Sex and gender differences in clinical and functional indices in subjects with schizophrenia and healthy controls: Data from the baseline and 4-year follow-up studies of the Italian Network for Research on Psychoses - Bucci, Paola; Giordano, Giulia Maria; Mucci, Armida; Rocca, Paola; Rossi, Alessandro; Bertolino, Alessandro; Aguglia, Eugenio; Altamura, Carlo; Amore, Mario; Bellomo, Antonello; Biondi, Massimo; Carpiniello, Bernardo; et al. (Schizophrenia research, 2023)
Gender differences in clinical and psychosocial aspects of schizophrenia have been widely reported. Findings have not always been consistent, and some of them need further research. In a large sample of community dwelling persons with schizophrenia, we investigated gender differences in clinical, cognitive and functional indices, as well as their changes over a 4-year follow-up and their impact on real-life functioning. Gender differences in personal resources, cognitive and functional indices were explored also in a sample of healthy controls. Men with respect to women had an earlier age of illness onset, a worse premorbid adjustment in the academic domain, more severe avolition, expressive deficit and positive symptoms, lower prevalence of comorbidity for affective disorders, less frequent use of two coping strategies (‘religion’ and ‘use of emotional support’) and more frequent positive history of substance and alcohol abuse. In addition, men were more impaired in verbal learning, while women in reasoning/problem solving. Some patterns of gender differences observed in healthy controls were not confirmed in patients. Men's disadvantages in the clinical picture did not translate into a worse outcome. This finding may be related to the complex interplay of several factors acting as predictors or mediators of outcome.